IPTEKS PERATURAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA MANADO PROVINSI SULAWESI UTARA - Kalalo, Angraini P.; Nangoi, Grace B. (Universitas Sam Ratulangi, 2018)
Tax is the responsibility of the people who are owed, either as individuals or business entities that aim to form laws, not directly and can be used for a large amount of people's prosperity. Payment of taxes is a manifestation of obligations and duties as well as tax obligations to participate and jointly. In accordance with the philosophy of the tax law, changing taxes is not only an obligation, but also for all countries for development.Keywords : Tax, Tax Regulations, and Taxpayer Awareness